Anisotropy of magnetic susceptibility: Application to tectonics and basin evolution - Reza Syahputra (Jurnal Geosains Terapan, 2023)
The anisotropy of magnetic susceptibility (AMS) was proposed over half a century ago and has earned tremendous popularity. The AMS method is a powerful quantitative tool for fabric analysis, especially in fine-grained sedimentary rocks that lack macroscopically observable paleocurrent indicators. In addition, the AMS has proven as an extremely sensitive indicator to record ‛invisible’ deformational fabrics. Thus, the AMS is increasingly used to characterize the preferred orientation of magnetic minerals from depositional to tectonic setting within a given basin, with the benefit of potentially recording weak upper-crustal strains. The AMS was tested in a sequential geological setting along the northern edge of Gondwana during the Neoproterozoic–Cambrian. The objective of this research is to find the timing and mechanism operated on the northern margin of Gondwana during active-pasive margin transition. In the Cadomian terranes, after the active Cadomian orogeny ceased, several diverse compositional plutons intruded the Teplá–Barrandian unit of the Bohemian Massif. The AMS data are able to differentiate the pre-, syn-, and post-plutonism structures (The Kdyně pluton, the Czech Republic). The possible geodynamic causes of this event were interpreted as a result of a slab break-off. Following this plutonism, the crust at the surface evolved as a graben-type structure of the Příbram–Jince basin (the Czech Republic). The AMS has successfully revealed the paleocurrent direction changes in this sedimentary basin, which was related to the change of tectonic regime.